EVOLUSI REGULASI PERBURUHAN DI INDONESIA: Evolution Of Labor Regulations In Indonesia - Isnaeni Lina Saputri; Wahyuni Retnowulandari (Faculty of Law, Universitas Trisakti, 2026)
The settlement of industrial relations disputes is a problem often faced by employers and workers. In Indonesia, common industrial relations problems include disputes over termination of employment, which have become a serious issue over time and have not been resolved despite regulations undergoing changes over several periods. The problem formulation in this paper concerns the historical periodization of the formation of regulations for the settlement of industrial relations disputes related to termination of employment in Indonesia. The research method uses a normative legal research type, focusing on historical methods, being descriptive in nature with conclusions drawn deductively. The results of the discussion and its conclusion are that Indonesian labor law has evolved from an exploitative colonial system to a more humane system. After the administrative era of P4D/P4P during the independence period and the New Order, the Reform era through Law No. 2 of 2004 shifted dispute resolution to the Industrial Relations Court. The procedure now requires bipartite and tripartite stages as primary requirements to ensure structured justice.